2005
DOI: 10.1037/0096-1523.31.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visual and Verbal Interaction on Unintentional Interpersonal Coordination.

Abstract: Previous research has demonstrated that people's movements can become unintentionally coordinated during interpersonal interaction. The current study sought to uncover the degree to which visual and verbal (conversation) interaction constrains and organizes the rhythmic limb movements of coactors. Two experiments were conducted in which pairs of participants completed an interpersonal puzzle task while swinging handheld pendulums with instructions that minimized intentional coordination but facilitated either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
261
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 285 publications
(287 citation statements)
references
References 77 publications
(124 reference statements)
18
261
1
1
Order By: Relevance
“…The point at which they make visual contact does not correspond, as far as we can determine, to any other change which would have resulted in the two groups being in stronger auditory contact. Although not conclusive in itself, this observation is consistent with other studies which have identified the role of visual attention in unintended interpersonal entrainment (Schmidt & O'Brien, 1997;Richardson et al, 2005Richardson et al, , 2007. In the third extract, when the two groups managed to resist entrainment, one of the strategies at play appears to be to avoid visual contact with the other group.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The point at which they make visual contact does not correspond, as far as we can determine, to any other change which would have resulted in the two groups being in stronger auditory contact. Although not conclusive in itself, this observation is consistent with other studies which have identified the role of visual attention in unintended interpersonal entrainment (Schmidt & O'Brien, 1997;Richardson et al, 2005Richardson et al, , 2007. In the third extract, when the two groups managed to resist entrainment, one of the strategies at play appears to be to avoid visual contact with the other group.…”
Section: Discussionsupporting
confidence: 72%
“…In terms of how the coupling occurs, in a musical context auditory information is of course important. However, a number of studies have pointed to the role of visual information in unintentional interpersonal coupling (Richardson et al, 2005;Richardson et al, 2007;Schmidt & O'Brien, 1997) and we have therefore also considered the likelihood that visual contact may have contributed to the instances of entrainment identified below.…”
Section: Introductionmentioning
confidence: 99%
“…Work on unintentional synchrony interpreted within a dynamical systems account suggests that the emergence of a coupled oscillator dynamic relies on visual information (Richardson et al, 2005;Schmidt & O'Brian, 1997). It remains to be seen whether interpersonal effects that result from the way task instructions are implemented can also be accounted for by dynamical systems principles.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the results reporting unintentional synchronization in humans are based on observation and categorization methods that rely primarily on the experimenter's appreciation of a given exemplar behavior rather than a quantitative measure of coupling and individual behavior (e.g. Barsalou et al, 2003;Condon & Sandler, 1974; but see Richardson, Marsh, & Schmidt, 2005).…”
Section: Introductionmentioning
confidence: 99%